Seven new narrowly endemic species of Gulella Pfeiffer, 1856 from eastern South Africa (Gastropoda, Streptaxidae) and status revision for another - Cole, Mary L.; Herbert, David G. (European Journal of Taxonomy, 2023)
Seven new species of very small Gulella Pfeiffer, 1856 are described from two regions in the interior of south-eastern South Africa within the Maputaland-Pondoland-Albany biodiversity hotspot. In addition, the status of Gulella darglensis benthodon van Bruggen, 1980 is revised and raised to species level. All species are very small-shelled and are narrow-range endemics. Six species, G. judithmastersae sp. nov., G. kevincolei sp. nov., G. hlathikhulu sp. nov., G. nkandla sp. nov., G. mystica sp. nov. and G. libertas sp. nov. are each known from only one locality. The first two as well as G. benthodon and G. mcmasteri sp. nov. are found only in the Amathole Mountains, where poaching, illegal harvesting of plant products and uncontrolled access of cattle take place, including in protected areas. The other four species each occur at one locality in north-central KwaZulu-Natal. The localities of three of the last-mentioned species are in protected areas although they are isolated and surrounded by a heavily transformed cultural landscape rendering enforcement of conservation legislation a challenge. Six species occur in nature reserves, highlighting the importance of small pockets of protected habitat for the conservation of terrestrial snails.